Study of Feminism and Women's Existence in the Novel Bumi Manusia by Pramoedya Ananta Toer - Yanuar Bagas Arwansyah; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2021)
Women are so close to idioms such as adversity, oppression, even to the